Determinants of economic integration in the Pacific Alliance 1990-2019 - et. al., Ricardo F. Cosio Borda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were: (a) To build the model that explains the intra-regional exports of the Pacific Alliance in the period 1990-2019; (b) To build the model that explains the intra-regional imports of the Pacific Alliance in the period 1990-2019; and, (c) To build the model that explains the coefficient of external openness of the Pacific Alliance countries in the period 1990-2019. Therefore, the positivist paradigm was applied, quantitative approach, substantive type, ex post facto non-experimental design and the method was hypothetical deductive. The data collection technique used was documentary analysis. The data were analyzed with the support of descriptive and inferential statistics. The results obtained showed three models, represented in the following equations: (a) Intraregional Export (X) = -406002,576 + 50,331 XT + 2,706 XNT - 28,769 IP - 13,667 PT - 15369,702 IPC; (b) Intraregional Imports (M) = -1030849.869 + 41530.637 IPC + 410.599 TC; and, (c) External Openness Coefficient (CAE) = 10.700 - 0.002 MBC + 0.157 TIR + 0.283 IPC - 0.004 TC. In conclusion, the research determined the three models that explain the variables that influence the integration process of the Pacific Alliance, based on the years from 1990 to 2019.